Endogenous estradiol in elderly individuals: Cognitive and noncognitive associations - V. Senanarong (2018)
Objective: To investigate an association between endogenous estradiol (E2) levels and cognition and behavior in elderly individuals. Patients: We studied 135 community-based men and women aged 52 to 85 years in urban Bangkok, Thailand; 72 had dementia and 63 did not. Materials and Methods: Dementia was diagnosed using Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, criteria after appropriate investigations. Blood samples for assay were collected in the morning after 6 hours of fasting. Levels of E2were measured by radioimmunoassay (double antibody technique). The Thai version of the Mini-Mental State Examination was used to assess cognition; the Neuropsychiatric Inventory was used to assess neuropsychiatric symptoms; and the Functional Assessment Questionnaire was used to assess instrumental activities of daily living. Results: There was no correlation between age and level of E2in either men or women. Individuals with lower estrogen levels had more behavioral disturbances (men: r = -0.467, n = 45; P = .001; women: r= -0.384, n = 90; P<.001) and worse cognition (men: r = 0.316, n = 45; P = .03; women: r = 0.243, n = 90; P= .02) and function (men: r = -0.417, n = 45; P =.004; women: r = -0.437, n = 90; P<.001). The threshold level of endogenous E2in elderly individuals for the risk of developing dementia was less than 15 pg/mL (<55 pmol/L) in men and less than 1 pg/mL (<4 pmol/L) in women. Conclusion: Lower E2levels are correlated with poor cognitive, behavioral, and functional status in older individuals.